2022
DOI: 10.1039/d2tc02729a
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent properties of single domain Fe2CoGa nanoparticles prepared by a facile template-less chemical route

Abstract: Single phase X type Fe2CoGa Heusler alloy nanoparticles with average crystallite sizes of 56 nm, 26 nm, and 21 nm have been synthesized using a refined template-less chemical route. Size...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 82 publications
(165 reference statements)
3
16
0
Order By: Relevance
“…The calculated values of K eff listed in Table show higher values compared to Fe 2 CoAl nanowires (= 4 × 10 3 J/m 3 ) . Since K eff values for Fe 2 CoAl nanoparticles are not available in the literature, a comparison is made with other Fe and Co-based Heusler alloy nanoparticles with high K eff . ,, The reason for such high K eff values can be credited to (i) a high S/V ratio which can give rise to broken exchange bonds at their surfaces, ,, (ii) high agglomeration of magnetic nanoparticles which can enhance interparticle interactions, and (iii) inter dipole interactions among the single-domain magnetic nanoparticles, etc. Table also reveals a decrement in K eff with D v .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated values of K eff listed in Table show higher values compared to Fe 2 CoAl nanowires (= 4 × 10 3 J/m 3 ) . Since K eff values for Fe 2 CoAl nanoparticles are not available in the literature, a comparison is made with other Fe and Co-based Heusler alloy nanoparticles with high K eff . ,, The reason for such high K eff values can be credited to (i) a high S/V ratio which can give rise to broken exchange bonds at their surfaces, ,, (ii) high agglomeration of magnetic nanoparticles which can enhance interparticle interactions, and (iii) inter dipole interactions among the single-domain magnetic nanoparticles, etc. Table also reveals a decrement in K eff with D v .…”
Section: Resultsmentioning
confidence: 99%
“…Using the values of A and D , D cr for Fe 2 CoAl alloy was evaluated to be 83 nm, which is higher than the crystallite size of the synthesized nanoparticles (see Table ), which authenticates that the produced nanoparticles are in a single-domain regime. The literature does not provide any approximated value of D cr , A , and D for Fe 2 CoAl nanoparticles to make a comparison, but the reported A and D values range for other Fe and Co-based Heusler nanoparticles as for Co 2 FeAl ( A = 12.0–17.5 × 10 –7 erg/cm; D = 7.850 × 10 –29 erg/cm 2 ), Fe 2 CoGa ( A = 5.39 × 10 –7 erg/cm; D = 2.89 × 10 –29 erg/cm 2 ), Co 2 FeGa ( D = 8.394 × 10 –29 erg/cm 2 ), Co 2 FeSi ( D = 3.653 × 10 –29 erg/cm 2 ), Co 2 MnAl ( A = 4.8 × 10 –7 erg/cm; D = 4.614 × 10 –29 erg/cm 2 ), Co 2 MnGa ( D = 4.229 × 10 –29 erg/cm 2 ), Co 2 MnGe ( A = 10.7–13.8 × 10 –7 erg/cm; A = 9.8 × 10 –7 erg/cm), Co 2 MnSi ( A = 23.5 × 10 –7 erg/cm; A = 4.6–5.0 × 10 –7 erg/cm; D = 5.367 × 10 –29 erg/cm 2 ), Co 2 CrGa ( D = 3.236 × 10 –29 erg/cm 2 ) validates our results.…”
Section: Resultsmentioning
confidence: 99%
“…Presence of a physical gap and a pseudo-gap like depression in the minority DOS at −0.8 eV (physical-gap) and +0.5 eV (pseudo-gap) can be seen for all three compositions. In the case of Fe 2 CoGa 0.5 Al 0.5 , both these gaps are slightly closer to E F (at −0.79 eV and +0.42 eV, respectively) than the end compounds (at −0.82 eV and +0.48 eV for Fe 2 CoGa 19 and at −0.83 eV and +0.46 eV for Fe 2 CoAl 20 ). Moreover, the minority DOS at the pseudo-gap at ∼0.5 eV less dense in Fe 2 CoGa 0.5 Al 0.5 (−0.33) than the end compounds Fe 2 CoGa 19 (−0.96) Fe 2 CoAl 20 (−0.81).…”
mentioning
confidence: 78%
“…Both the end compositions Fe 2 CoGa and Fe 2 CoAl are known to be non-half-metallic as shown in our previous studies. 19,20 However, some earlier studies have demonstrated superior half-metallic characteristics and spin polarization ( P ) in intermediate quaternary compositions such as Co 2 FeGa x Ge 1− x as compared to the ternary end compositions. 36 Therefore, ab initio calculations were performed on Fe 2 CoGa 0.5 Al 0.5 as per the procedure described in the experimental and computational section using the experimentally determined lattice constant a .…”
mentioning
confidence: 99%
See 1 more Smart Citation